Utilization, Demand, And Willingness to Pay for Telehealth Services: A Study of Patients in Selected Vietnamese Provinces - Hung Ta; Hoan Van Vu; Thu Xuan Mai; Hieu Thi Minh Nguyen; Toan Thanh Thi Do; Hoat Ngoc Luu (Asia Pacific Journal of Health Management)
Objective: Telehealth has become essential in healthcare delivery, particularly during the COVID-19 pandemic. It provides solutions to access disruptions and enhances healthcare accessibility and efficiency. This study aimed to describe the utilization, demand, and willingness to pay for Telehealth services in selected provinces in Vietnam.